Fundus image enhancement using white top hat operation and perona-malik diffusion filter - Anam, Syaiful; Fitriah, Zuraidah; Shofianah, Nur; Bagus Edy Wibowo, Ratno (International Journal of Engineering and Technology, 2019)
Diabetes mellitus is a chronic disease characterized by increasing the blood sugar levels that are far above normal. The diabetes mellitus can damage small blood vessels in the retina called diabetic retinopathy. The diabetic retinopathy could result in blurred vision and can progress to blindness when it is left untreated. The diabetic retinopathy is one of the main causes of blindness in the western world in the working period population. One way to find out the diabetic retinopathy is by examining the eye fundus image with using a fundus camera. However, the fundus image often has noise and uneven illumination which cause the evaluation diabetic retinopathy is hard. Therefore, a method for enhancing the fundus image is necessary. This paper proposes the use of white top operation and the Perona - Malik diffusion filters for enhancing the quality of the fundus image. The white top-hat transform is used to extracts small elements and details from given images. The Perona–Malik diffusion filter is used for reducing the noise in images without removing significant parts of the image contents. From the results of experiment, it can be concluded that the proposed method is able to significantly improve fundus image.
Keywords: Diabetic Retinopathy; Fundus Image; Image Enhancement; Perona-Malik Diffusion Filter; White Top Hat Operation.